Synthesis and Study of some Heterocyclic Compounds from Schiff Base of Pinacolone - N.G. Ahmad; H.S. Aziz; G. Th. Sedeek (Tikrit Journal of Pure Science)
In this work, the synthesis of some heterocyclic compound of four, five and seven membered rings were done. On oxidation of the pinacole alcohol using concentrated sulphuric acid pinacolone were obtained and used as a precursor for the synthesis of three new Schiffs base through the reaction with para substituted anilines compounds. These imines were allowed to react with chloroacetyl chloride in dry dioxane to give the azetadine -2- one compounds. Also some thiazoldinone compounds were synthesized from the reaction of the corresponding imines with thioglycolic acid in the presence of zinc chloride in dry benzene and 1, 3-oxazepine-4,7-diones, were obtained from the reaction of imines with maleic and phythalic anhydries in dry benzene. The synthesized compounds were characterized by IR spectroscopy and physical paramrters.